Male Factor Infertility and Semen Analysis among Infertile Male Subjects - Hussain, Nafeesa Binti; Zinan, Aklima Zakaria (Journal of Chittagong Medical College Teachers' Association, 2021)
Background: The prevalence of infertility in the general population is 15% -20%,of this the male factor is responsible for 20%-40%. Semen analysis is an indispensable diagnostic tool in the evaluation of male partner of infertile couple.Every single couple out of 10 is in search of medical care because of infertility. Men older than 40 years and Women older than 30 years are at an increased risk of infertility. So objective of the present study was to see the different risk factors and sperm count of male infertility. Materials and methods: Current cross sectional observational study is design to figure out existence, problems and causes, associated with male infertility among 120 male subjects done during two years study period from January 2018 to December 2020 in a Teriarty Medical College and some private chambers of Bangladesh. After consent different health data were recorded and semen analysis was done For this purpose, survey has been conducted at different private hospitals and private chambers were selected for further studies.Semen sample were analyzed by manual method. Ethical clearance was taken from the hospital authorities to conduct the study Results: Among 120 subjects 76(63.3%) subjects was at age group 31-40 years and 44(36.7%) was at age group 41 50 years. Different occupations of the study subjects revealed 42(35.0%) were banker, 37(30%) were doing business and 41(34.2%) were involved in other services. Regarding different comorbidities, HTN was present in 18(15%), 3(2.5%) had bronchial asthma, 3(2.5% had DM, 3(2.5%) had HTN with DM and 90(75%) had none and 54(45%) were smoker. Sperm analysis revealed 50(41.7%) had asthenozoospermia, 12(10%) had Asthenozoospermia +Teratospermia, 16 (13.3%) had oligopsermia, 17(14.2%) had Oligospermia+ Asthenozoospermia 8(6.7%) had Oligospermia +Teratospermia and 17(14.2%) had teratospermia. Sperm count among the subjects revealed 23(19.2%) had <10 million/ml, 18(15%) had 11-20 million/ml, 18(15%) had 21-30 million/ml, 15(12.5%) had 31-40 million/ml, 9(7.5%) had 41-50 million/ ml, 13(10.8%) had 51-60 million/ml and 24(20%) had >60 million/ml. Conclusion: It is concluded that male infertility is independent on the age factor but excessive use of tobacco, sedentary life style like Banking , stress or psychological disturbances might provoke issues of infertility. JCMCTA 2021 ; 32 (2) : 75-78